An Unusual Combination of Three Rare Complications: Pleuro-Pancreatic Fistula, Chylous Ascites, and Renal Vein Thrombosis, in a Case of Acute Severe Pancreatitis - Huda, Tanweerul; Mohan, Anjaly; Parwez, Mohammad Masoom; Pandya, Bharati (The Surgery Journal, 2019)
Background Acute pancreatitis is fraught with a variety of complications, which account for the mortality associated. Our case had a fulminant course, with three rare, near-fatal complications and was successfully managed conservatively. Pleural effusion due to pleuro-pancreatic fistula is uncommon, seen in only 1% cases, of which right-sided effusions are rarer still. Management modalities include conservative, endoscopic, and surgical options. Chylous ascites is an extremely rare complication of pancreatitis and is managed with high protein, low lipid diet, restricted to medium-chain triglycerides (MCTs). Extra-splanchnic venous thrombosis is uncommon in pancreatitis, and isolated renal vein thrombosis is very rare.Case Presentation A 34-year-old, chronic alcoholic male, presented to the outpatient department (OPD) in a state of shock and respiratory distress. Chest radiograph showed massive right-sided pleural effusion. The pleural fluid was hemorrhagic with markedly elevated amylase levels, and contrast-enhanced computed tomography (CECT) confirmed the presence of a right-sided pleuro-pancreatic fistula. Left renal vein thrombosis was also noted. The patient improved with chest drain, intravenous (IV) octreotide, and anticoagulants. Subsequently, he developed hemorrhagic pancreatic ascites, which later turned chylous. This was managed with dietary modifications. The patient had a prolonged recovery but was finally discharged after 45 days.Conclusion It is a challenge managing the various complications of acute severe pancreatitis. We describe this case to emphasize maintaining a high sensitivity for timely diagnosis and appropriate addressal of all the complications for better patient outcomes.
Keywords: acute pancreatitis; pleuro-pancreatic fistula; pancreatic ascites; chylous ascites; renal vein thrombosis